A chemokine-dependent stromal induction mechanism for aberrant lymphocyte accumulation and compromised lymphatic return in rheumatoid arthritis. - Burman, A; Haworth, O; Hardie, D; Amft, E; Siewert, C; Jackson, D; Salmon, M; Buckley, C (2005)
According to the current model for tissue-specific homing, specificity is conferred by the selective recruitment of lymphocyte populations from peripheral blood, based on their expression of chemokine and adhesion receptors (endothelial selection). In this study, we provide evidence for an alternative stromal induction mechanism that operates in chronic inflammation. We show that the human rheumatoid synovial microenvironment directly induces functional inflammatory (CCR5 and CXCR3) and constitutive (CCR7 and CXCR4) chemokine receptors on infiltrating CD4(+) T cells. Expression of the corresponding inflammatory chemokine ligands (CCL5 and CXCL11) was confined to stromal areas in the synovium. However, expression of the constitutive ligands (CCL19 and CXCL12) was inappropriately high on both vascular and lymphatic endothelium, suggesting that the vascular to lymphatic chemokine gradient involved in lymphatic recirculation becomes subverted in the rheumatoid synovium. These results challenge the view that leukocyte trafficking is regulated solely by selective recruitment of pre-existing chemokine receptor-positive cells from peripheral blood, by providing an alternative explanation based on aberrant lymphocyte retention and compromised lymphatic return.